Distribution of aquatic macrophytes in the coastal area of Salimpur, Chittagong, Bangladesh. - Abu Hena, Mustafa Kamal; Aysha, A.; Ashraful, M. A. K.; Sharifuzzaman, S. M. (Chiang Mai University, 2010)
This preliminary study was conducted to investigate the distribution pattern of the aquatic macrophytes in the inter-tidal coastal belt of Salimpur, Chittagong. During this study, 3 species of mangrove, i.e., Sonaratia apetala, Avicennia marina and Acanthus ilicifolius, 1 species of wild rice related to salt marsh grass, i.e., Porteresia coarctata, 3 species of macro-algae, i.e., Ulva intestinalis, Catenella nipae and Dictyota dichotoma and 1 species of poison lily Crinum defixum were identified from this coast. The dominant macrophyte was planted Sonaratia apetala, followed by Porteresia coarctata in the coast line of Salimpur. Considering from the ecological and economic view, especially Catenella nipae, could be an important living resource for cultivation and sea ranching in this area. Besides, the importance of these aquatic inter-tidal macrophytes for fishery resources and overall ecosystem processes should not be over looked in this coastal area.